From clear lakes to murky waters – tracing the functional response of high‐latitude lake communities to concurrent 'greening' and 'browning'. (21st February 2019) - Hayden, B.; Harrod, C.; Thomas, S. M.; Eloranta, A. P.; Myllykangas, J.‐P.; Siwertsson, A.; Præbel, K.; Knudsen, R.; Amundsen, P.‐A.; Kahilainen, K. K.
Abstract: Climate change and the intensification of land use practices are causing widespread eutrophication of subarctic lakes. The implications of this rapid change for lake ecosystem function remain poorly understood. To assess how freshwater communities respond to such profound changes in their habitat and resource availability, we conducted a space‐for‐time analysis of food‐web structure in 30 lakes situated across a temperature‐productivity gradient equivalent to the predicted future climate of subarctic Europe (temperature +3°C, precipitation +30% and nutrient +45 μg L −1 total phosphorus). Along this gradient, we observed an increase in the assimilation of pelagic‐derived carbon from 25 to 75% throughout primary, secondary and tertiary consumers. This shift was overwhelmingly driven by the consumption of pelagic detritus by benthic primary consumers and was not accompanied by increased pelagic foraging by higher trophic level consumers. Our data also revealed a convergence of the carbon isotope ratios of pelagic and benthic food web endmembers in the warmest, most productive lakes indicating that the incorporation of terrestrial derived carbon into aquatic food webs increases as land use intensifies. These results, reflecting changes along a gradient characteristic of the predicted future environment throughout the subarctic, indicate that climate and land use driven eutrophication and browning are radically altering the function and fuelling of aquatic food webs in this biome.